Insecticide resistance and genetic structure of Aedes aegypti populations from Rio de Janeiro State, Brazil. - Rafi Ur Rahman; Luciano Veiga Cosme; Monique Melo Costa; Luana Carrara; José Bento Pereira Lima; Ademir Jesus Martins (Public Library of Science (PLoS), 2021)
Vector control largely relies on neurotoxic chemicals, and insecticide resistance (IR) directly threatens their effectiveness. In some cases, specific alleles cause IR, and knowledge of the genetic diversity and gene flow among mosquito populations is crucial to track their arrival, rise, and spread. Here we evaluated Aedes aegypti populations' susceptibility status, collected in 2016 from six different municipalities of Rio de Janeiro state (RJ), to temephos, pyriproxyfen, malathion, and deltamethrin. We collected eggs of Ae. aegypti in Campos dos Goytacazes (Cgy), Itaperuna (Ipn), Iguaba Grande (Igg), Itaboraí (Ibr), Mangaratiba (Mgr), and Vassouras (Vsr). We followed the World Health Organization (WHO) guidelines and investigated the degree of susceptibility/resistance of mosquitoes to these insecticides. We used the Rockefeller strain as a susceptible positive control. We genotyped the V1016I and F1534C knockdown resistance (kdr) alleles using qPCR TaqMan SNP genotyping assay. Besides, with the use of Ae. aegypti SNP-chip, we performed genomic population analyses by genotyping more than 15,000 biallelic SNPs in mosquitoes from each population. We added previous data from populations from other countries to evaluate the ancestry of RJ populations. All RJ Ae. aegypti populations were susceptible to pyriproxyfen and malathion and highly resistant to deltamethrin. The resistance ratios for temephos was below 3,0 in Cgy, Ibr, and Igg populations, representing the lowest rates since IR monitoring started in this Brazilian region. We found the kdr alleles in high frequencies in all populations, partially justifying the observed resistance to pyrethroid. Population genetics analysis showed that Ae. aegypti revealed potential higher migration among some RJ localities and low genetic structure for most of them. Future population genetic studies, together with IR data in Ae aegypti on a broader scale, can help us predict the gene flow within and among the Brazilian States, allowing us to track the dynamics of arrival and changes in the frequency of IR alleles, and providing critical information to improving vector control program.